Factors influencing adoption of cloud computing services in HEIs: a UTAUT approach based on students' perception. (10th January 2023) - Kabra, Gaurav; Ghosh, Vinit; Joshi, Yatish
The use of cloud computing services in higher education institutions (HEIs) is gaining momentum. From a stakeholder analysis perspective, this study aims to advance the understanding of students' intentions to adopt cloud technologies. By extending the unified theory of acceptance and use of technology (UTAUT) framework, we have tried to investigate the interplay and influence of students' cognitive factors in explaining their perception towards cloud adoption. The data sample consisted of 190 undergraduate students from Indian educational institutes. The findings revealed that social influence, performance expectancy and facilitating conditions are positively related to the attitude towards cloud adoption. Moreover, the positive effect of facilitating conditions on students' attitude is mediated by perceived trust. It was also found that performance expectancy of cloud-enabled learning mediates the effects of social influence on students' attitude towards the latest technology. The present study has profound implications on HEI's change management plans and can design ways for the seamless integration of learning functions using cloud technologies.